Sandwich-like hierarchical porous dual-carbon catalyst with more accessible sites for boosting oxygen reduction reaction. (September 2021) - Gai, Huiyu; Xue, Song; Wang, Xingkun; Zhou, Jian; Jiang, Heqing; Huang, Minghua
Abstract: Fabricating highly efficient catalysts toward oxygen reduction reaction (ORR), especially carbon-based metal-free ones, plays a crucial role in large-scale applications of various renewable energy conversion devices. However, the poor electrocatalytic performance of these carbon catalysts severely hinders their application because most active sites are deeply buried inside the carbon framework and fail to be accessible for the reactants. In this work, we fabricate multimodally porous N-doped dual-carbon catalyst with a sandwich-like structure, that is, N-doped mesoporous carbon spheres loaded on reduced graphene oxide nanosheets (N-MCS@rGO). The obtained catalysts exhibit interconnected hierarchical microporous/mesoporous/macroporous structure and a high specific surface area, which can simultaneously maximize the efficient utilization of active sites and facilitate mass transport, resulting in superior alkaline ORR activities. The half-wave potential of the N-MCS@rGO was ~0.85 V vs. reversible hydrogen electrode (RHE) in 0.1 M KOH, preceding most of the non-noble metal catalysts and comparable with ~0.86 V vs. RHE of commercial 20 wt% Pt/C catalysts. The established Zn-air batteries using the N-MCS@rGO as the air cathode exhibit a high power density of 100 mW/cm 2, outperforming the commercial Pt/C catalyst-based battery. This work supplies an interesting avenue in the rational construction of multidimensional hierarchically porous materials for advanced energy conversion technologies. Graphical abstract: Image 1 Highlights: N-doped mesoporous carbon spheres on reduced graphene oxide nanosheet was prepared via electrostatic self-assembly strategy. The hierarchical porous structures can maximize the efficient utilization of active sites and facilitate the mass transport. The N-MCS@rGO-based ZABs afford the high power density and long-term stability.